Deciphering hydrothermal Te-Bi bonanza mineralization: In situ trace element and sulfur isotope evidence from the Dashuigou deposit, SW China - Zhao, Qingqing; Zhai, Degao; Keith, Manuel; Voudouris, Panagiotis; Tombros, Stylianos; Liu, Jiajun (Mineralium Deposita, 2025)
The genesis of high-grade tellurium-bismuth (Te-Bi) deposits, which are globally rare, remains poorly understood. The Dashuigou deposit in Sichuan, southwestern China, stands out as the only known independent Te-Bi deposit in the country, hosting substantial reserves of Te (508 tons at 1.17 wt.%) and Bi (768 tons at 1.76 wt.%). Despite its significance, the sources of these metals and the mechanisms of Te-Bi enrichment remain unclear. Three hypogene ore stages have been identified: stage I pyrrhotite + pyrite + dolomite, stage II tetradymite + tsumoite + pyrite + dolomite + muscovite, and stage III quartz + calcite. Pyrite exhibits distinct textural variations across these stages, with euhedral forms characterizing stage I and colloform textures defining stage II. In situ S isotope analysis of pyrite from stages I and II revealed a δ34S range of -0.5 to 5.1‰ (median = 4.0‰), corresponding to a calculated fluid δ34SH2S value of 2.5‰ that is consistent with a magmatic S source, which may have also contributed substantial amounts of Te and Bi. The limited δ34S variability within individual pyrite crystals further suggests that S was derived from a homogenous source. Textural and geochemical data indicate that stage I euhedral pyrite, enriched in Co (median = 5950 ppm) but depleted in Ni, Te, Bi, and Au, precipitated from an early, metal-poor hydrothermal fluid. In contrast, the rims of stage II colloform pyrite contain significantly higher concentrations of Te, Bi, and Au, indicating influx of a metal-rich fluid during the later stages of mineralization. Elevated fTe2 values were likely critical in triggering the Te-Bi precipitation. We propose that rapid fluid cooling ultimately induced supersaturation, promoting the formation of colloform pyrite and facilitating extreme Te-Bi enrichment. We conclude that under such conditions, Bi-Te colloids may have formed in the ore-forming fluid, contributing to the exceptional metal enrichment at Dashuigou and similar deposits worldwide.
CRIS-Team Scopus Importer:2025-10-24
Keywords: Dashuigou; Sulfur isotopes; SW China; Te-Bi deposits; Trace elements